Image comparisons among analysis, simulation and experimental solutions about stress distribution in rings loaded by multiple symmetrical radial forces - Sun, Yica; Jiao, Yongshu; Peng, Wang; Dongqing, Pang (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The theorem of energy valley state and a particular solution of Airy biharmonic equation will be used in the stress analysis in the rings loaded by the multiple- fold symmetrical forces to obtain stresses formulas. The varied stress graphs have been plotted with these formulas and FEM, revealing their periods of symmetry of forces.